ESSENTIAL STRATEGIES FOR TEACHING STUDENTS TO READ - Minotti, Tony (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This paper examines ways to help elementary school students in the Osaka region of Japan learn to read in English. The need for this research has become important because of the mandate from the Ministry of Education to implement English in the elementary school curriculum as of April 2020. The methodology used was an exploration of a cause-and-effect relationship between the techniques used by the teacher and the student’s ability to learn to read. The findings show that, by using phonics, analogy phonics, context clues, syntax, and sight words, children in the Kids’ English Program at Osaka Shoin Women’s University (OSWU) showed an improvement in their reading skills. One takeaway from this research was that, when students had long periods off between their lessons, there was a decrease in their reading abilities.